New product concept selection: an integrated approach using data envelopment analysis (DEA) and conjoint analysis (CA) - Salhieh, SaEd M.; Al-Harris, Mira Y. (International Journal of Engineering and Technology, 2014)
New product concept development is considered to be a critical step and the main determinant for the success or failure of new product development. This paper introduces a new methodology for the evaluation and selection of new product concepts using Data Envelopment Analysis (DEA) and Conjoint Analysis (CA). The proposed methodology integrates customer perceived value of the new product concepts through the use of CA and uses this perceived value as a measure for the new concepts’ performance. In addition, the methodology takes into account the development burden that a company has to perform to bring the new concept into a state of market readiness. This development burden is estimated by determining two main factors, namely the burden to produce and the burden to sell the new product concept. The customer perceived value and the development burden are both used in DEA to evaluate the new product concepts resulting in the selection of the best product concept. The applicability of the proposed methodology is illustrated through a case study.   Keywords: Product development, concept selection, data envelopment analysis, conjoint analysis.